2010
DOI: 10.1002/jso.21727
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of neoadjuvant therapy for extended hepatic metastases—have we reached our (non‐resectable) limit?

Abstract: Surgical resection offers the best chance for cure in patients with colorectal liver metastases; however, only 15-25% of them can benefit from surgery. To increase resectability a number of strategies have been developed in different fields including chemotherapy, surgery, and radiology. Bringing them together into an integrated framework has expanded the number of patients that can be treated with curative intent. This review focuses on recent oncosurgical changes, their impact, and future directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 94 publications
3
29
0
3
Order By: Relevance
“…Bismuth et al [13] reported that 17% of patients with NRLM were eligible for hepatectomy after treatment with FOLFOX, offering benefit in survival. Recent reports show that the S14 Tech Coloproctol (2011) 15 (Suppl 1):S13-S16 usage of FOLFOX, FOLFIRI or even FOLFIRINOX combined with biologic agents greatly improves the response rates, and almost 30% of patients with NRLM are eligible for resection [16]. There is much debate about the extent of liver resection needed in patients who have responded to preoperative chemotherapy or ever ''cured''.…”
Section: Neoadjuvant Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Bismuth et al [13] reported that 17% of patients with NRLM were eligible for hepatectomy after treatment with FOLFOX, offering benefit in survival. Recent reports show that the S14 Tech Coloproctol (2011) 15 (Suppl 1):S13-S16 usage of FOLFOX, FOLFIRI or even FOLFIRINOX combined with biologic agents greatly improves the response rates, and almost 30% of patients with NRLM are eligible for resection [16]. There is much debate about the extent of liver resection needed in patients who have responded to preoperative chemotherapy or ever ''cured''.…”
Section: Neoadjuvant Chemotherapymentioning
confidence: 99%
“…It is indicated when the FLR volume after resection is below the cutoff values of 20% for normal liver parenchyma and 30-40% in patients underwent preoperative chemotherapy or have abnormal liver parenchyma (usually patients with cirrhosis) [2,4,5]. A possible complication of PVE is tumor progression in the FLR as a result of the induced liver hypertrophy when bilobar CRLM are present [2,16,17].…”
Section: Portal Vein Embolizationmentioning
confidence: 99%
“…das postoperative Überleben zu verbessern (z.B. adjuvante Chemotherapie beim Pankreaskarzinom [6,10] [20]. Interessanterweise kam es trotz mehrfacher Veröffentlichung der Daten zu keiner deutlichen Verände-rung des Einweisungsverhaltens und damit des Anteils an Patienten, die an Low-volume-Zentren operiert wurden [20].…”
Section: Hepato-pankreatiko-biliäre Chirurgie Im Fokus Der Zentrumsbiunclassified
“…3,4 Several clinical studies have shown that the association of chemotherapy with bevacizumab (vascular endothelial growth factor monoclonal antibody), or cetuximab [epidermal growth factor receptor (EGFR) monoclonal antibody] is particularly promising in improving the resectability rate and, ultimately, survival.…”
mentioning
confidence: 99%
“…3,4 Several clinical studies have shown that the association of chemotherapy with bevacizumab (vascular endothelial growth factor monoclonal antibody), or cetuximab [epidermal growth factor receptor (EGFR) monoclonal antibody] is particularly promising in improving the resectability rate and, ultimately, survival. 5 Panitumumab is a fully human monoclonal antibody that binds specifically to the EGFR, and consequently, severe panitumumab-related infusion reactions are rare.…”
mentioning
confidence: 99%